208 DBS-Induced Improvement in Cognitive Control is Mediated by Theta Oscillations in Human Intracranial Recordings. (April 2023) - Allawala, Anusha; Vartany, Stephanie; Mathura, Raissa; Ritz, Harrison; Adkinson, Joshua; Gadot, Ron; Oswalt, Denise; Shenhav, Amitai; Goodman, Wayne; Pouratian, Nader; Bijanki, Kelly R.; Borton, David; et al.
Abstract : INTRODUCTION: Deficits in cognitive control, defined as the ability to adjust response or attention in the face of competing or changing demands, are thought to be responsible for inflexible behaviors in neuropsychiatric diseases. Here, we seek to understand frontotemporal networks underlying dysfunctional cognitive function using sEEG recordings and deep brain stimulation (DBS) in human subjects with treatment-resistant depression (TRD). METHODS: We employed a forced two-choice cognitive control task where the strength in the target and the distractor interference of a visual stimulus was parametrically and independently varied, resulting in granular variation in response congruence. This task was performed in 13 total subjects, 10 of whom underwent sEEG implants for epilepsy monitoring, whereas 3 subjects were participating in a clinical trial of DBS for TRD and were additionally implanted with DBS leads in the ventral capsule/ventral striatum and subcallosal cingulate. RESULTS: Reaction time (RT) and accuracy worsened with increasing levels of conflict across all subjects (Cohen's d-accuracy = 0.7, Cohen's d-RT = 0.2) prior to stimulation. Single-trial regression analyses revealed a parametric effect of task conflict with theta-band (4-7 Hz) power across the dorsolateral PFC (dlPFC), dorsal anterior cingulate cortex, orbitofrontal cortex (OFC) as well as the insula. DBS significantly improved behavioral performance, demonstrated by reduced RT (1080 土 10 ms to 840 土 50 ms), and improved accuracy(70 土 9.8% to 90 土 5%). While we observed an overall increase in theta power across the PFC and ACC in TRD participants following DBS, the effect of conflict in theta power was reversed (theta power decreased with increasing conflict in dlPFC and OFC). CONCLUSIONS: Leveraging this unique behavioral paradigm with concurrent distributed intracranial recordings and causal manipulation broadens our understanding of neural substrates of decision-making as well as the mechanisms of therapeutic action of DBS for TRD and other psychiatric disorders.